The Private Equity market in Europe. Rise of a new cycle or tail of the recession? - Anastasia Di Carlo (European Investment Fund (EIF), 2010)
This paper presents a general overview of the European Private Equity (PE) market as of September 2009, based on industry activity data published by the European Venture Capital Association (EVCA) in November 2009 and the latest performance data published by Thomson Reuters Venture Xpert as of June 2009. The financial system and public equity markets seem to have now stabilised and a slow recovery is expected in 2010. However, the main characteristic of the current global recession is uncertainty, and it is still too early to confirm a turnaround. Private Equity is a cyclical industry and the findings of the analysis show that a floor has probably been reached. However, the medium-term performance outlook remains uncertain. Therefore, funds are looking towards governments and institutional investors for support due to the increased challenging fundraising environment. The paper is organised as follows: a brief introduction on the global macroeconomic outlook and the responses to the financial crisis is followed by an overview of the main trends currently observed in the Private Equity market. The analysis focuses on two major dimensions: activity figures (fundraising, investments and divestments) and performance figures (rolling investment horizon). Finally, some recommendations conclude the paper. A Private Equity glossary according to EVCA definitions is attached to this paper in Annex 3.
Keywords: 330